An Efflux Pumps Inhibitor Significantly Improved the Antibacterial Activity of Botanicals from Plectranthus glandulosus towards MDR Phenotypes. (11th May 2021) - Nanmeni, Gravalain; Tedonkeu, Alex T.; Fankam, Aimé G.; Mbaveng, Armelle T.; Wamba, Brice E. N.; Nayim, Paul; Bitchagno, Gabin T. M.; Nzogong, Raïssa T.; Awouafack, Maurice D.; Tene, Mathieu; Beng, Veronique P.; Kuete, Victor
Abstract : Bacterial multidrug resistance causes many therapeutic failures, making it more difficult to fight against bacterial diseases. This study aimed to investigate the antibacterial activity of extract, fractions, and phytochemicals from Plectranthus glandulosus (Lamiaceae) against multidrug-resistant (MDR) Gram-negative phenotypes expressing efflux pumps. The crude extract after extraction was subjected to column chromatography, and the structures of the isolated compounds were determined using spectrometric and spectroscopic techniques. Antibacterial assays of samples alone and in the presence of an efflux pump inhibitor (phenylalanine-arginine β -naphthylamide, PA β N) were carried out using the broth microdilution method. The phytochemical study of P. glandulosus plant extract afforded seven major fractions (A–G) which lead to the isolation of seventeen known compounds. The ethanol extract of P. glandulosus was not active at up to 1024  μ g/mL, whereas its fractions showed MICs varying from 32 to 512  μ g/mL on the studied bacteria. Fraction C of P. glandulosus showed the lowest MIC (32  μ g/mL) on E. coli ATCC8739 strain. Fraction D presented the highest activity spectrum by inhibiting the growth of 90% (9/10) of the studied bacteria. The presence of PA β N has improved the activity of extract and all fractions. Overall, the tested phytochemicals showed low activity against the studied bacteria. The overall results obtained in this study show that some fractions from P. glandulosus, mainly fractions C and D, should be investigated more for their possible use to fight against MDR bacteria.